Patient characteristics, predictors and outcome of pacemaker patients upgraded to an implantable cardioverter defibrillator. (19th May 2022) - Baldinger, SH; Burren, D; Noti, F; Servatius, H; Seiler, J; Madaffari, A; Asatryan, B; Tanner, H; Reichlin, T; Haeberlin, A; Roten, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pacemaker (PM) patients may require a later upgrade to an implantable cardioverter-defibrillator (ICD). Limited data exists on this patient population. We sought to characterize this population, to assess predictors for ICD upgrade, and to report the outcome. Methods: From our prospective PM and ICD implantation registry, all patients who underwent PM and/or ICD implantations at our center were analyzed. Patient characteristics and outcome of PM patients with subsequent ICD upgrade were compared to age- and sex-matched patients with de novo ICD implantation, and to PM patients without later upgrade. Results: Of 1'301 ICD implantations, 60 (5%) were upgrades from PMs. Median time from PM implantation to ICD upgrade was 2.6 years (IQR 1.3-5.4) Of 2'195 PM patients, 28 patients underwent subsequent ICD upgrade, corresponding to an estimated annual incidence of an ICD upgrade of at least 0.33%. Lower LVEF (p=0.05) and male sex (p=0.038) were independent predictors for ICD upgrade. Transplant- and LVAD-free survival was worse both for upgraded ICD patients compared to matched patients with de novo ICD implantation (p=0.05; Figure, panel A), as well as for PM patients with later upgrade compared to matched PM patients not requiring an upgrade (p=0.036; Figure, panel B). Conclusions: One of twenty ICD implantations are upgrades of patients with a PM. At least one of 30 PM patients will require an ICD upgrade in the following 10 years. Predictors for ICD upgrade are male sex and lower LVEF at PM implantation. Upgraded patients have worse outcome.